Inside the eyes - Halvorson, Karin, 1979- (Minneapolis, Minn. : ABDO Pub. Co., 2013)
Provides an introduction to the human eye, discussing its structure, and it works.
Your body -- All about the eye -- Socket to me! -- Keep it clean -- Fast focus -- Light the way -- See change -- The color of light -- Get focused! -- Eye spy -- Rods & cones -- Seeing stars -- Spin cycle -- Eye can do it! you can too!.
Library Media Connection starred, November 2013
Horn Book, November 2013
3.3
K-3
590L
Keywords: Eye -- Juvenile literature; Vision -- Juvenile literature; Eye; Vision